1991
DOI: 10.1113/expphysiol.1991.sp003556
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon 1‐21 reduces intestinal epithelial cell proliferation in parenterally fed rats

Abstract: SUMMARYThe hypothesis that glucagon 1-21 (GI-21) is trophic to the gastrointestinal tract was investigated in the hypoplastic intestine of intravenously maintained rats. Three groups of eight rats were fed parenterally for three days and then were infused with either 0, 20 or 80,ug rat-1 day-1 of G1-21 for 3 days. No significant effect on the weight of the stomach, caecum or colon was observed, but both the weight and crypt cell production rate of the small intestine were significantly decreased by G1-21. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…1988 ) incubated with enteroglucagon. In contrast, studies in vivo failed to show any trophic actions of glucagon on cell proliferation ( Goodlad et al . 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…1988 ) incubated with enteroglucagon. In contrast, studies in vivo failed to show any trophic actions of glucagon on cell proliferation ( Goodlad et al . 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological actions of enteroglucagon remain unclear, as Gregor et al [29] and Goodlad et al [30] reported no trophic effects of enteroglucagon on the small intestine. In the future, this ELISA method for quantifying plasma glicentin levels will make it easier to clarify the role of glicentin in other intestinal diseases or some other postoperative status.…”
Section: Discussionmentioning
confidence: 99%